Safety and efficacy of a feed additive consisting of fumaric acid for all animal species for the renewal of its authorisation and extension of use (Life SUPPLIES NV) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the assessment of the application for the renewal of the authorisation of fumaric acid as a technological and sensory additive (functional groups: preservative and flavouring compounds, respectively) and for a new use of the additive as a technological additive (functional group: acidity regulator) for all animal species. The applicant provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that fumaric acid remains safe under the authorised conditions of use for the terrestrial animals, consumers and the environment. However, the Panel cannot conclude on the safety for the aquatic animals under all authorised condition of use. Fumaric acid is irritant to skin, eyes and respiratory tract, and should be considered a skin and respiratory sensitiser due to the presence of nickel. The Panel also considers that the new use of the additive as an acidity regulator under proposed conditions of use would not introduce risks not already considered. There is no need to assess the efficacy of the additive in the context of the renewal of the authorisation (for its use as preservative and flavouring compound). The Panel is not in the position to conclude on the efficacy of fumaric acid as an acidity regulator in feed.